Estratégias biotecnológicas para a liberação controlada de antígenos e adjuvantes em vacinas através de lipossomas - Formariz, Thalita Pedroni [UNESP]; Terruggi, Cristina Helena Bruno [UNESP]; Silva Jr., Arnóbio Antonio [UNESP]; Scarpa, Maria Virgínia [UNESP]; Oliveira, Anselmo Gomes de [UNESP] (My University, 2006)
Liposomes (LP) are colloidal systems with ability to compartmentalize therapeutic molecules in order to improve biological activity, decreases the potential toxicity, and to obtain prolonged effect. In this work it was discussed the role of the various liposomes types to encapsulate drug molecules able to provoke some immunological response (drugs, antigens and DNA). The effect of the liposomes and the parameters about the formation of the structures are also analyzed. Detailed literature review shows that, depending on the molecules polarity and the superficial charge of the liposome structures, the system may be efficiently used to optimize the therapeutic effects by means of the release control or through a drug delivery mechanism.
Biotechnological strategies for controlled delivery of antigens and vaccines adjuvant through liposomes
Keywords: Controlled release; Immunology; Liposomes; antigen; liposome; vaccine; drug activity; drug delivery system; drug effect; drug release; encapsulation